2019
DOI: 10.14324/111.444.amps.2019v16i1.003
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and Conservation in Contemporary Cities: A(n) (Im)possible Coupling

Abstract: Cities are built by and for able-bodied people and are often composed of a range of elements that make them partially (or not) accessible to disabled people. Architectural barriers within and around buildings can limit disabled people’s access to structures and services, precluding their full participation in a social life. It is not possible to talk about making further social progress until disabled people are no longer victims of marginalisation caused by our urban architecture. In order to identify some sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…However, there were some elements that appeared to be problematic for the majority of participants, regardless of disability type and other participant characteristics. Many of these barriers correspond with what is already known from the literature, such as uneven flooring (pavement), steps, particularly at shop entrances ( 9 , 12 , 13 , 18 ), as well as objects on sidewalks ( 9 , 19 ) and the lack of accessible toilets ( 13 , 42 ). However, some participants ignored some obstacles that were obvious for the research team, such as access to certain shops or restaurants with steps at the entrance.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…However, there were some elements that appeared to be problematic for the majority of participants, regardless of disability type and other participant characteristics. Many of these barriers correspond with what is already known from the literature, such as uneven flooring (pavement), steps, particularly at shop entrances ( 9 , 12 , 13 , 18 ), as well as objects on sidewalks ( 9 , 19 ) and the lack of accessible toilets ( 13 , 42 ). However, some participants ignored some obstacles that were obvious for the research team, such as access to certain shops or restaurants with steps at the entrance.…”
Section: Discussionsupporting
confidence: 64%
“…But also, historic heritage places have different functions associated to several categories such as residence, education, health and research, religion, community, government activities or transportation, among others ( 8 ). Since historic heritage places have various functions, many activities such as tourism and cultural leisure, education, work, participation in the political life, may be restricted for people with disabilities ( 9 ). Moreover, heritage places are usually protected, and they cannot be modified, so adaptations to make them accessible constitute a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether impaired people are efficiently connected in their micro activity is also a concern. It should be accessible for them to reach the building entrance as uncomplicated as possible [7]. As we know, people have outdoor activities and have a relation with buildings and infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is on the importance of evaluating Malaysia's cultural heritage DOI: 10.15320/ICONARP.2022.228 structures in the context of accessible tourism. The study mentions that restorations to make historic cities accessible in Northern Italy have not been carried out (Pretto, 2019). It is also revealed that it is possible to make the necessary architectural arrangements in a very short time and at cheap costs.…”
Section: Introductionmentioning
confidence: 99%